(untitled) (Memorias Sifored - Encuentros Educación UAN, 2023)
The results of the ICFES tests show that rural schools are below the national average in the mathematics component, which leads us to question the teaching techniques used in the classroom. A compilation of 12 articles describing different teaching techniques applied in different rural areas of Colombia was carried out. As a first finding, we found that the contents should be adapted to the student’s context, then the articles were classified into three categories: TIC’s, realistic mathematics education and gamification. It is worth noting that each category has a totally different didactic approach and allows for innovation in teaching practices. We conclude that there are different techniques that allow the development of mathematical skills in the student, complementing traditional methods, establishing links between the theoretical and the student’s daily life.